Cortisol, glicose e triglicerídeo na resposta neuroendócrina de cães com fratura tibial - Sturion, André Luiz Torrecillas (2011)
"Response to stress" is the designation for the set of metabolic and hormonal changes that take place after any traumatic situation. The stress response is intended to maintain and / or restore the homeostasis of the body injured. The major endocrine response to stress is characterized as the increased secretion of pituitary hormones and activation of the sympathetic nervous system. Among the pituitary hormones is ACTH, which will sensitize the cells of the adrenal gland to secrete cortisol. The biochemical measurements, especially cortisol and glucose has been shown to be important references for the evaluation of pain and stress by indirect means. Therefore, the objective of this research is to measure cortisol, the glucose and triglyceride metabolic energy, in evaluating the neuroendocrine response of dogs with tibial fractures. For the present study, we used 12 dogs with tibial fractures. Were colected five venous blood samples, at the time of patient care, during the surgical procedure after induction of anesthesia, five minutes after stimulation by periosteal implant, 24 hours after the first collection during surgery and after seven days of the surgery. There were no statistically significant differences between times and between the values of cortisol, glucose and triglycerides, but there was a numerical difference between the mean times analyzed, we observed that the cortisol showed an average decrease between times. The mean glucose values had increased in the pre and trans-surgical times, and with a decrease in mean postoperative periods. Mean triglyceride values varied widely between periods. It is possible to conclude that cortisol is an important mediator in the neuroendocrine response of dogs with acute tibial fractures, the mean values of glucose did not respond similarly to cortisol during surgical procedures and that the triglyceride is not a good parameter for evaluating the neuroendocrine stress dogs with acute tibial fractures.